Beginning Google Web Toolkit - Smeets, Bram (Springer, 2017)
The open source, lightweight Google Web Toolkit (GWT) is a framework that allows Java developers to build rich Internet applications (RIAs), more recently called Ajax applications, in Java. Typically, writing these applications requires a lot of JavaScript development. However, Java and JavaScript are very distinctively different languages (although the name suggests otherwise), therefore requiring a different development process.